“Wireline + Wireless” Networking Remote Monitoring Technology for Analysing the Unloading Deformation Characteristics of the Fractured Surrounding Rock Mass Induced by Underground Excavation - Bin Hu; Jianlong Sheng; Jing Li; Peng-Zhi Pan; Guangquan Zhang; Zuyang Ye (Advances in Civil Engineering)
Collapse or large deformation of fractured surrounding rock mass occurs frequently in underground tunnelling and results in many casualties and extensive property damage. This paper proposed a new type of remote telemetry system for monitoring the mechanical responses of underground tunnels during unloading. This system adopted both wired and wireless networking schemes, including a signal collection and transmission subsystem, a management analysis subsystem, and a remote receiving subsystem, in the tunnels. The application of this new approach in a subway tunnel indicated that the complete unloading performance of a surrounding rock mass can be captured in real time and high frequency using this method, recording the deformation of the surrounding rock, the stress in the bolts, and the stress in the shotcrete between the surrounding rock and steel arch. The in situ experimental study also found that deformation of the fractured surrounding rock mass in the Dashizi Tunnel showed a step-like fluctuating growth pattern. Additionally, the mechanical response of the surrounding rock mass during unloading tended to stabilize when the opening face was approximately 35 m away from the monitoring section, providing new ways to optimize the excavation process and support measured.